Correction to: Stable Zn Metal Anodes with Limited Zn-Doping in MgF2 Interphase for Fast and Uniformly Ionic Flux - Kim, Ji Young; Liu, Guicheng; Ardhi, Ryanda Enggar Anugrah; Park, Jihun; Kim, Hansung; Lee, Joong Kee (Nano-Micro Letters, 2022)
The practical applications of aqueous Zn metal batteries are currently restricted by the inherent drawbacks of Zn such as the hydrogen evolution reaction, sluggish kinetics, and dendrite formation. To address these problems, herein, a limitedly Zn-doped MgF2 interphase comprising an upper region of pure, porous MgF2 and a lower region of gradient Zn-doped MgF2 is achieved via radio frequency sputtering technique. The porous MgF2 region is a polar insulator whose high corrosion resistance facilitates the de-solvation of the solvated Zn ions and suppression of hydrogen evolution, resulting in Zn metal electrodes with a low interfacial resistance. The Zn-doped MgF2 region facilitates fast transfer kinetics and homogeneous deposition of Zn ions owing to the interfacial polarization between the Zn dopant and MgF2 matrix, and the high concentration of the Zn dopant on the surface of the metal substrate as fine nuclei. Consequently, a symmetric cell incorporating the proposed Zn metal exhibits low overpotentials of ~ 27.2 and ~ 99.7 mV without Zn dendrites over 250 to 8000 cycles at current densities of 1.0 and 10.0 mA cm−2, respectively. The developed Zn/MnO2 full cell exhibits superior capacity retentions of 97.5% and 84.0% with average Coulombic efficiencies of 99.96% after 1000 and 3000 cycles, respectively. Highlights: 1 A limitedly Zn-doped MgF2 passivation layer consisting of a porous pure MgF2- and gradient Zn-doped MgF2-regions was developed for stable Zn metal anodes with excellent reversibility to 8000 cycles at 10.0 mA cm−2. 2 The MgF2 region facilitates facile de-solvation of Zn ions and effective hydrogen evolution reaction suppression. 3 The Zn-doped MgF2 region enhances transfer kinetics and homogeneous deposition of Zn ions by interfacial polarization between Zn dopant and MgF2 matrix, and high concentration of the Zn dopant as fine nuclei.